Uma abordagem sobre sistemas de numeração - Tavares, Adriano Carneiro (2014)
This paper presents the numbering systems, their criteria and applications for teaching basic mathematics. We study problems involving number systems and operations. We focus on the high school students from state schools. We present a simple and brief, a few techniques for solving problems with the operations of arithmetic. This approach is done through games and curiosity of mathematics. We cite the Russian multiplication table. We have a theoretical basis the ideas of Henri Wallon that prey upon affectivity and dynamism by the teacher-student dialogue and student-student. This dynamism is made in the implementation of recreational activities such as math games that involve drawing, magic and divination. We also present the criteria for divisibility, the idea of greatest common divisor and least common multiple, and the use of the concepts of set theory.